2020
DOI: 10.3390/molecules25235607
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Coupled Quartz-Enhanced Photoacoustic Spectroscopy System for Methane and Ethane Monitoring in the Near-Infrared Spectral Range

Abstract: We report on a fiber-coupled, quartz-enhanced photoacoustic spectroscopy (QEPAS) near-IR sensor for sequential detection of methane (CH4 or C1) and ethane (C2H6 or C2) in air. With the aim of developing a lightweight, compact, low-power-consumption sensor suitable for unmanned aerial vehicles (UAVs)-empowered environmental monitoring, an all-fiber configuration was designed and realized. Two laser diodes emitting at 1653.7 nm and 1684 nm for CH4 and C2H6 detection, respectively, were fiber-combined and fiber-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…A detailed comparison between the demonstrated OA-ICOS sensor system and other previously reported dual-gas CH 4 /C 2 H 6 sensors are summarized in Table . Though there are differences in the light source and absorption path length (centimeters to tens of kilometers), the developed sensor possesses the lowest detection limit for CH 4 detection, and almost the lowest detection limit for C 2 H 6 detection. Furthermore, this sensor is the only one with the functions of mobile inspection and NG leakage source location at the same time for ppbv-level CH 4 /C 2 H 6 detection.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…A detailed comparison between the demonstrated OA-ICOS sensor system and other previously reported dual-gas CH 4 /C 2 H 6 sensors are summarized in Table . Though there are differences in the light source and absorption path length (centimeters to tens of kilometers), the developed sensor possesses the lowest detection limit for CH 4 detection, and almost the lowest detection limit for C 2 H 6 detection. Furthermore, this sensor is the only one with the functions of mobile inspection and NG leakage source location at the same time for ppbv-level CH 4 /C 2 H 6 detection.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Being beneficial from the features and advantages, QEPAS has been proposed for field applications in monitoring sour gas (H 2 S, CO 2 ) in an offshore riser, downhole gas analysis, early fire, leak detection, and health-safety-environment monitoring . A typical QEPAS sensor system can be compacted in a small size with light weight, supporting the deployment of the sensor in a portable analyzer, a downhole tool, and an unmanned aerial vehicle. , Several real-world applications of QEPAS have already been reported, , including carbon monoxide (CO) detection in urban area, monitoring of methane (CH 4 ) in landfills, and leak detection of sulfur hexafluoride (SF 6 ) in a vacuum-seal test station for diesel engine injector.…”
Section: Conclusion and The Way Forwardmentioning
confidence: 99%
“…29 A typical QEPAS sensor system can be compacted in a small size with light weight, supporting the deployment of the sensor in a portable analyzer, a downhole tool, and an unmanned aerial vehicle. 23,34 Several real-world applications of QEPAS have already been reported, 35,36 including carbon monoxide (CO) detection in urban area, monitoring of methane (CH 4 ) in landfills, and leak detection of sulfur hexafluoride (SF 6 ) in a vacuum-seal test station for diesel engine injector.…”
Section: ■ Author Informationmentioning
confidence: 99%
“…Schematic diagram of near‐infrared fiber based QEPAS sensing system: (A) multi‐component QEPAS sensing system for CH 4 and NH 3 monitoring 46 ; (B) multi‐component QEPAS sensing system for CH 4 and C 2 H 6 monitoring 47 ; (C) multi‐point QEPAS sensing system. Reproduced from Reference 48, with the permission of AIP Publishing [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Fiber‐based Qepas Sensing Systemmentioning
confidence: 99%
“…Since the transmission of optical fiber provides great convenience for multi‐component gas detection, 2020, Gansergio et al 47 reported a fiber‐based QEPAS system, which can monitor methane and ethane at the same time. The structure of which is shown in Figure 2(B).…”
Section: Fiber‐based Qepas Sensing Systemmentioning
confidence: 99%